Empowering STEM education through the role of principals: a systematic literature review - Talib, Sariati; Alias, Bity Salwana; Matore, Mohd Effendi Ewan Mohd; Abdullah, Abdul Halim (Journal of Education and Learning (EduLearn), 2025)
Science, technology, engineering, and mathematics (STEM) education is increasingly recognized as a critical topic in today's educational landscape. This is because contemporary education outcomes need to equip students for the demands of 21st-century jobs. In this context, the role and strategic actions of school principals emerge as critical factors in the success of implementing and empowering STEM education initiatives. The roles and strategies of principals from various aspects need to be explored. Therefore, this study aims to delve deep into the roles and strategies of principals from various contexts through research conducted from 2021 to 2024. This study analyzes past research findings through the systematic literature review (SLR) method. The research findings indicate that a total of 20 articles reveal various roles and strategies of principals. These include leadership management, professional development, fostering a STEM-focused culture, and refining assessment methods. These findings underscore the importance of active involvement in optimizing the roles and strategies of principals across various aspects. Thus, effective STEM education relies on the commitment of principals in managing various aspects, shaping a conducive culture, and facilitating teacher development. Recognizing and embracing the multifaceted roles are paramount in navigating challenges and ensuring the effectiveness of STEM programs.